Craftivism Between Nationalism and Activism in Ukraine and Belarus - Myzelev, Alla (Frontiers in Sociology, 2022)
Ukraine’s Feminist Body in the Media: FEMEN and Transnational Feminism A group of Ukrainian radical feminists, known as FEMEN, became a household name both in the West and Ukraine through digitally translated images of their protests. Often topless, always provocatively dressed these women loudly demonstrated against issues such as sex tourism and sex trafficking, corruption, social sexism, and homophobia. Based in Ukraine and later in Paris, since 2010 they became synonymous with the most notorious use of the nude bodies to fight feminist issues. Such turn to the embodied protest came as a surprise to the Western countries, or at least to USA and Canada, where the use of the body in the feminist struggle was considered to be outdated. New types of feminist critics were usually intersectional and considered more "dignified". Yet, this type of embodied protest was influential enough on the Western Feminism that rallies of "slut walk" started as early as 2011. In the interviews, the early leaders of the rallies listed FEMEN as their supporters and inspiration. FEMEN’s protests, which, importantly, are shown to most of the public through the eye of a camera, either professional and amateur, pose a conundrum for a feminist art historian who studies Eastern Europe. How did this group rose in a country, that had very little in a way of feminist tradition compared to the West? Did the innovative and controversial use of the bodies could only rise in the country where Marxist, political, and social feminism had roots in the soviet style of equality? Is the use of the beautiful, objectified bodies of FEMEN subverts the hypersexuality that some Eastern European women are known for? Finally, how does one understand the national belonging expressed by their members by wearing the traditional Ukrainian headpiece during the protests? How does one reconcile national belonging with international presence both in the protests and thus on the screens?